Detection of gene amplification in MYCN, C-MYC, MYCL1, ERBB2, EGFR, AKT2, and human papilloma virus in samples from cervical smear normal cytology, intraepithelial cervical neoplasia (CIN I, II, III), and cervical cancer (Colombia Medica, 2011)
Introduction: Cervical cancer is the second most common cancer among women worldwide and the second cause of cancer mortality in women. It has been demonstrated that the process of cervical carcinogenesis displays genetic and environmental epigenetic components. Currently, research is focused on new prognosis markers like oncogene amplification. Objectives: To perform detection of MYCN, C-MYC, MYCL1, ERBB2, EGFR, and AKT2 amplification. Additionally, to detect human papillomavirus in samples from normal cytology smear, cervical intraepithelial neoplasia (CIN) I, II, and III and cervical cancer patients. Methods: Papillomavirus (HPV) genotyping by reverse line blot (RLB) performed and gene amplification by detection with real-time PCR with Taqman probes. Results: HPV was present in 4% of the patients with normal cytology, 48% in CIN I, 63.6% in CIN II, 64% in CIN III, and 70.8% in cervical cancer. Genes amplified in cervical cancer were MYCN (39.1%), ERBB2 (34.7%), and MYCL1 (30.4%); showed higher amplification in high-grade lesions and cervical cancer in relation to low-grade lesions and normal cytology with statistically significant differences. Besides the genes, C-MYC, EGFR, and AKT2 were amplified in samples from patients with cervical cancer by 12%, 18%, and 13%, respectively; we did not find statistical differences. Conclusion: Higher prevalence of gene amplification and HPV was found in high-grade cervical lesions and cervical cancer.